A conversation with 590 nascent entrepreneurs - Jeffrey R. Campbell; Mariacristina De Nardi (Federal Reserve Bank of Chicago, 2007)
This paper summarizes interviews from 1998 with 590 individuals trying to create a business centered around five questions: 'Who are you?', 'What are you trying to accomplish?', 'What have you and others put into the business?', 'What have you accomplished?', 'What remains to be done?' There is a great deal of heterogeneity across these Nascent entrepreneurs, but they tend to have more education than the general population. Growing up in a family in which one or both parents had a business does not seem to be an important determinant of entry into entrepreneurship for males, while it seems to be of some importance for females. Most of the nascent businesses are in retail and consumer services, and about 50 percent of nascent entrepreneurs expect to become employers within five years of the business's birth. Most nascent entrepreneurs have already made personally-significant investments of time and money in their firms; and nearly all of them are saving for their firms out of non-business income. For about half of the sample, these investments have yielded a fully-specified product; and the remainder are still in the product development stage. Family and friends are an importance source of seed money for many Nascent Entrepreneurs. Formal credit markets have been requested for funds only by a minority of Nascent Entrepreneurs, and almost half of these applicants have been denied loans. About 40% of the Nascent Entrepreneurs believe that their businesses require significantly greater equity before they can attract external funds.
Keywords: L26; M13; 330; Panel Study of Entrepreneurial Dynamics; Entry; Business Credit